Personal Control as a Mediator Between Perceptions of Supervisory Behaviors and Employee Reactions - Greenberger, David B.; Strasser, Stephen; Lee, Soonmook (Academy of Management Journal, 1988)
The article assesses the construct of personal control in an organizational setting using a base model of personal control in organizations. The difference between control possessed and control desired is examined, and a discussion is presented about the measurement of contingent and noncontingent supervisory behaviors. The author presents the results of goodness of fit and Chi-square difference tests for null and modified models. The article focuses on the perceptions of supervisor's behavior by subordinates.